Improving hand hygiene of young children with a digital intervention: a cluster-randomised controlled field trial - Graichen, Joanna (Springer Nature, 2025)
Contagious diseases that affect young children place a great burden on them and their families. Proper hand hygiene is an important measure to reduce the disease burden, however, its implementation in day care centres is challenging. This paper introduces a digital intervention to support independent and good handwashing among young children. The intervention leverages animated instructions triggered by water and soap use, together with a symbolic reward shown to children on a screen during and immediately after handwashing. We tested the intervention in a pre-registered, cluster-randomised controlled field trial in 4 day care centres in Finland and Germany with 162 children over 42 days. The intervention increased soaping time, used as a proxy for handwashing quality, by 5.30 s (+ 62%, p < 0.001). The effect occurs immediately at the onset of the intervention and is maintained throughout the intervention phase.